The Evolution of Modern Linguistics: Key Concepts and Trends (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article explores the evolution of modern linguistics, highlighting key developments, methodologies, and interdisciplinary trends in the study of language. It examines foundational branches such as phonetics, syntax, semantics, sociolinguistics, and psycholinguistics, while also discussing emerging fields like computational linguistics and the impact of artificial intelligence on language research. The article emphasizes the shift towards more cognitive, socially oriented, and technology-driven approaches to linguistics, noting the rise of cognitive linguistics, language documentation, and the intersection of linguistics with AI and machine learning. The paper concludes by considering future directions for the field, including the continued importance of language diversity, the relationship between language and identity, and the growing role of interdisciplinary collaboration.